2017
DOI: 10.3389/fmicb.2017.01102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phenazine-1-Carboxylic Acid on Mycelial Growth of Botrytis cinerea Produced by Pseudomonas aeruginosa LV Strain

Abstract: One of the most important postharvest plant pathogens that affect strawberries, grapes and tomatoes is Botrytis cinerea, known as gray mold. The fungus remains in latent form until spore germination conditions are good, making infection control difficult, causing great losses in the whole production chain. This study aimed to purify and identify phenazine-1-carboxylic acid (PCA) produced by the Pseudomonas aeruginosa LV strain and to determine its antifungal activity against B. cinerea. The compounds produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…Commercial standard lipopeptides (surfactin and iturin, Sigma-Aldrich, United States) and CLE methanol solution (10 mg/L) were run on an HPLC system (Waters, E2695, United States) with a C 18 reverse-phase column (5 µm, 4.6 × 150 mm) und er the same conditions(46). Water and acetonitrile were selected as the mobile phase at a ratio of 20:80 by volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial standard lipopeptides (surfactin and iturin, Sigma-Aldrich, United States) and CLE methanol solution (10 mg/L) were run on an HPLC system (Waters, E2695, United States) with a C 18 reverse-phase column (5 µm, 4.6 × 150 mm) und er the same conditions(46). Water and acetonitrile were selected as the mobile phase at a ratio of 20:80 by volume.…”
Section: Methodsmentioning
confidence: 99%
“…The injection volume was 1 mL per min, and the eluate was monitored at 214 nm. According to the peak times of standard lipopeptides, the peaks of potential lipopeptides contained in CLE were collected and dried at room temperature(45, 46).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate if the level of reporter activity could be used to estimate levels of the biosynthetic product, β ‐galactosidase‐mediated indication of recombinant phenazine production in P. putida KT2440 was chosen as an example. The chorismic acid‐derived group of phenazine compounds displays antibacterial and antifungal properties (Simionato et al ., ; Zhang et al ., ; Zhu et al ., ) and P. putida KT2440, a safe and widely established representative workhorse of the Pseudomonas clade, is able to withstand production of the compound (Domröse et al ., ).…”
Section: An Example Of Ytrex Application: Generation and Lacz‐based Cmentioning
confidence: 99%
“…Recent research has shown strain of Pseudomonas aeruginosa secreting an organometallic compound with inhibitory activity against MDR bacteria, including carbapenemase-producing Klebsiella pneumoniae and methicillin-resistant Staphylococcus aureus [9,10]. Additionally, the same strain produced a phenazine-1-carboxylic acid (in low quantity) showing antifungal potential against Botrytis cinerea [11,12].…”
Section: Beneficial Roles Of Pseudomonas Species In Medicinementioning
confidence: 99%